GAWI SABUMI EDUCATIONAL ANIMATION: STRENGTHENING STUDENTS CULTURAL LITERACY ON BANJAR PHILOSOPHY - Ferdiyansyah, Aldy; Iskandar, Bagus Aulia (Universitas Labuhanbatu, 2025)
Purpose – This study examines the effectiveness of the GAWI SABUMI educational animation video in strengthening students' cultural literacy related to the philosophy of the Banjar community. The study was motivated by findings that students' cultural literacy remains low, especially in internalizing the values of GAWI SABUMI, due to the limited availability of engaging and contextual learning media.Methodology – A Research and Development (R&D) approach was applied using the DDD-E model (decide, design, develop, evaluate). The participants consisted of 60 undergraduate students from the Elementary School Teacher Education Program at Lambung Mangkurat University, divided into two groups: 30 in the experimental class and 30 in the control class. Data were collected through expert validation questionnaires and pre- and post–test assessments. Cultural literacy was assessed through three indicators: understanding cultural complexity, knowledge of one's own culture, and cultural awareness. Data analysis was conducted using the Wilcoxon and Mann-Whitney tests, along with N-Gain calculations.Findings – The results showed improvement in both groups, but the experimental class demonstrated more substantial gains. The Wilcoxon test indicated significant differences between pretest and posttest scores in both classes, with Z = -3.898 (Sig. = 0.000) for the control group and Z = -4.816 (Sig. = 0.000) for the experimental group. The higher Z value in the experimental class reflects greater effectiveness. The Mann-Whitney test confirmed a significant difference between the two groups (Sig. = 0.000 < 0.05). The average N-Gain of 0.83 in the experimental group fell into the high category, indicating the substantial effectiveness of the animation video.Contribution – This study contributes to the development of innovative, local wisdom-based learning media. It highlights the potential of animation as a pedagogical tool for internalizing cultural values, particularly Banjar philosophy, in higher education.